Effect Of Complementary Therapy On Hypertension Patients: Systematic Review - Al Ihksan Agus; Wa Ode Sri Asnaniar; Rizqy Iftitah Alam; Haeril Amir (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The research was conducted using the method literature review. The literature review examines various research reports published in journals with the same focus. jurnal studies related to complementary therapies in patients with hypertension, international journal using Pubmed database, derect Science, Wiley, and DOAJ. The keywords used are "Hypertension AND Complementary Therapy". After filtering according to the research criteria, 8 journals that are relevant and worthy of review are obtained. The most effective use of therapy among the elderly is therapy using herbal medicine because herbal therapy is easy to reach and cheap and can even be obtained free of charge around the neighborhood. However, as it is known that hypertension is one of the diseases related to the circulatory system so that the elderly still need conventional therapy to assist in controlling blood pressure and exercise therapy or holistic therapy